Using CuO nanoparticles and hyperthermia in radiotherapy of MCF-7 cell line: synergistic effect in cancer therapy - Hadi Esmaeili Govarchin Ghaleh; Leila Zarei; Bahman Mansori Motlagh; Nasrollah Jabbari (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
The aim of this paper was examining the combined impacts of CuO nanoparticles (CuO NPs), hyperthermia (H), and irradiation (R) on an increment of MCF-7 cells. The MTT assay was employed to assess the antiproliferative effects of CuO NPs (25, 50, and 100 μg/ml), hyperthermia (41 °C for 1 h), and irradiation (200 cGy). Moreover, the perniciousness was estimated through the survival capability of cells, and apoptosis, ROS production, and levels of caspase-3, -8 and -9 proteins were determined. A significant (p < .01) decrease in proliferation index (0.124 ± 0.021), a significant (p < .01) increase in apoptosis (42% ± 1.54) of MCF7 cells, a significant (p < .03) increase in ROS formation (32.16 ± 1.9) and a significant (p < .01) increase in LDH release (33.28 ± 1.56) were recorded in the adjacency of MCF-7 cells by a combination of CuO NPs (100 µg/ml) and R + H compared to control and other treatments. The activities of caspase-3 (0.33 ± 0.014) and caspase-9 (0.389 ± 0.019) also increased significantly (p < .05). However, caspase-8 showed no significant changes in its activity (p = .065). Based on these observations, a combination of CuO NPs, hyperthermia, and irradiation could suppress the growth of MCF-7 cells and evoke cell apoptosis via mitochondrial membrane potential.